KOMPUTASI KERUGIAN LINTASAN SINYAL DENGAN MODEL HATA - Suhartono, Suhartono (MATEMATIKA, 2009)
Signal is a wave that can be expressed by physical phenomenon. Mathematically signal wave can be represented as a function of single or many independent variables, for example signal wave over building as a function of distance or time. In fact, signal spreading as a wave have many attenuation, for example is caused by difraction  when the signal over the urban area or building. The purpose of the research  is to present  the signal path loss model in the urban area by using Hata model. The  result of the computation has shown  that the decreasing of the  signal  path  loss in urban area can be effected by  the increasing of  the receiver antenna height.